ISLAND VALUES IN LAM MIM ALIF FILM BASED ON JOHN FISKE SEMIOTIC ANALYSIS - Ali Imran Sinaga; Ricka Puspita Dewi (Universitas Dharmawangsa, 2020)
The object of research is the video footage of the film Alif Lam Mim and the unit of analysis pieces of images in films which are believed to give birth to debate or pros and cons. From the results of research in assessing Islamic values, found Individual Islamic values, found in the character of Alif that is sincere. Islamic values in the Family, found in Lam figures who provide moral education to their children by freeing their opinions and practicing their way of thinking. Social Islamic values, found in the figure of three small children, who give kindness and say hello to fellow Muslims. Islamic values in the State, there is in the figure Alif who reprimanded anyone who did wrong in the duties of the state, even though his own boss. Islamic values of Religion are found in the Mim leaders who believe in Him and depend on the future for His will, which is described in terms of patience, obedience, and sincerity.